2016
DOI: 10.1515/hmbci-2016-0017
|View full text |Cite
|
Sign up to set email alerts
|

Primary umbilical endometriosis successfully treated with dienogest

Abstract: Primary umbilical endometriosis (PUE) is a rare gynaecological disorder. A majority of the reported cases were treated with surgical excision as medical treatment had been found to be less successful. We reported a case of PUE successfully treated with dienogest without any profound side effects from the drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Medical management widely used hormonal therapy like oral contraceptive pills, dienogest and GnRH antagonist have been mentioned in literature and have been effective in relieving the symptoms but disease progression is not halted by medical therapy so recurrence of symptoms and growth of lesions is the major drawback [16] .…”
Section: Discussionmentioning
confidence: 99%
“…Medical management widely used hormonal therapy like oral contraceptive pills, dienogest and GnRH antagonist have been mentioned in literature and have been effective in relieving the symptoms but disease progression is not halted by medical therapy so recurrence of symptoms and growth of lesions is the major drawback [16] .…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-nine published studies with primary umbilical endometriosis were identified in the literature written in English and Korean language during the period 2000~2016 ( Table 1 ) 1 3 4 5 6 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 . Primary umbilical endometriosis is initially very rare condition, but it is now increasing in number.…”
Section: Discussionmentioning
confidence: 99%
“…In a review of PUE literature published during the period 2015-2020, seventeen studies were identified written in English or French language (Table 1) [9,13,[22][23][24][26][27][28][29][30][31][32][33][34][35][36][37]. Based on all reports, the mean age of patients with PUE was 36.3 years.…”
Section: Discussionmentioning
confidence: 99%